Evaluation of weekend admission on the prevalence of hospital acquired conditions in patients receiving thoracolumbar fusions. Issue 8 (August 2015) - Attenello, Frank J.; Wen, Timothy; Huang, Christina; Cen, Steven; Mack, William J.; Acosta, Frank L.
Abstract: We evaluated the Nationwide Inpatient Sample (NIS) database for increased hospital acquired condition (HAC) rate as a function of weekend admission in patients receiving thoracolumbar fusions. In 2008, the Centers for Medicare and Medicaid Services (CMS) compiled a list of HAC for a new payment policy for preventable adverse events without reimbursement of resulting hospital costs. In this, the thoracolumbar patients represented a population with significant increased rates of HAC and, to our knowledge, no prior studies have evaluated the effect of weekend admission on HAC rate. We collated data for patients who underwent thoracolumbar fusions from the 2002–2010 NIS database. Using CMS definitions, HAC were abstracted using the Ninth Edition of International Classification of Diseases Clinical Modification (ICD-9CM). Multivariate analysis assessed the impact of a weekend admission on HAC occurrence and prolonged length of stay (LOS) adjusting for patient, admission severity, and hospital covariates. There were 1, 842, 231 total admissions between 2002 and 2010 associated with thoracolumbar procedures. HAC occurred at a frequency of 5.2% overall. Surgical site infections (n = 10, 656) and falls/trauma (n = 83, 999) were the most common. After adjusting for disease severity and urgency of admission, patients admitted on the weekend were more than two times more likely to incur a HAC compared to those admitted on weekdays (odds ratio 2.41; 95% confidence interval 2.19–2.65; p  < 0.05). HAC occurrence and weekend admission were also associated with prolonged LOS ( p  < 0.05). We found that weekend admission is associated with increased HAC rate. Though our conclusions must be tempered by limitations of the coded national database, further study is warranted to confirm this disparity and evaluate potential for improvement.